Wheelchair Supplier Selection Using the Analytical Hierarchy Process Method - Juwita, Isna; Linda, Rozza; Okrianto, Engki (Journal of Information System, Technology and Engineering, 2024)
This study is about the analysis of wheelchair supplier selection using the analytical hierarchy process (AHP) method. It has been conducted at CV. Calvino Medika Indonesia within 3 months. The problem in this study is that there are no criteria for selecting wheelchair suppliers, so that supplier performance is not optimal; wheelchair suppliers have not been the best. The aim of this study is to develop a series of crucial selection criteria for wheelchair suppliers. Determine the right wheelchair supplier. The study's sample consisted of individuals working in the administration and sales marketing divisions, as well as the Director of CV at Calvino Medika Indonesia. The data collection techniques used in this study included observation and questionnaires. Expert choice software and MS Excel processing support the purposive sampling method in this study. The results of this study are as follows: The most influential criteria in selecting wheelchair suppliers are quality criteria (36.1%), the second priority that influences is price (27.2%), the third priority that influences is delivery (18.2%), the fourth priority that influences is adaptive (7.60%), and the fifth priority that influences is service (27.2%). Based on the criteria and sub-criteria used in supplier selection, PT Inti Sumber Hasil Sempurna emerges as the top supplier, scoring 59.2%, while PT. Asada Putra Mandiri comes in second, scoring 40.8%.